Associations of Physical Activity With Survival and Progression in Metastatic Colorectal Cancer: Results From Cancer and Leukemia Group B (Alliance)/SWOG 80405 - Guercio, Brendan J. (J Clin Oncol, 2019)
PURPOSE: Regular physical activity is associated with reduced risk of recurrence and mortality in patients with nonmetastatic colorectal cancer. Its influence on patients with advanced/metastatic colorectal cancer (mCRC) has been largely unexplored. PATIENTS AND METHODS: We conducted a prospective cohort study nested in Cancer and Leukemia Group B (Alliance)/SWOG 80405 (ClinicalTrials.gov identifier: NCT00265850), a National Cancer Institute–sponsored phase III trial of systemic therapy for mCRC. Within 1 month after therapy initiation, patients were invited to complete a validated questionnaire that reported average physical activity over the previous 2 months. On the basis of responses, we calculated metabolic equivalent task (MET) hours per week to quantify physical activity. The primary end point of the clinical trial and this companion study was overall survival (OS). Secondary end points included progression-free survival (PFS) and first grade 3 or greater treatment-related adverse events. To minimize confounding by poor and declining health, we excluded patients who experienced progression or died within 60 days of activity assessment and used Cox proportional hazards regression analysis to adjust for known prognostic factors, comorbidities, and weight loss. RESULTS: The final cohort included 1,218 patients. Compared with patients engaged in less than 3 MET hours per week of physical activity, patients engaged in 18 or more MET hours per week experienced an adjusted hazard ratio for OS of 0.85 (95% CI, 0.71 to 1.02; P(Trend) = .06) and for PFS of 0.83 (95% CI, 0.70 to 0.99; P(Trend) = .01). Compared with patients engaging in less than 9 MET hours per week, patients engaging in 9 or more MET hours per week experienced an adjusted hazard ratio for grade 3 or greater treatment-related adverse events of 0.73 (95% CI, 0.62 to 0.86; P(Trend) < .001). CONCLUSION: Among patients with mCRC in Cancer and Leukemia Group B (Alliance)/SWOG 80405, association of physical activity with OS was not statistically significant. Greater physical activity was associated with longer PFS and lower adjusted risk for first grade 3 or greater treatment-related adverse events.